God, Being, and the 'End of Metaphysics' Paul Ricoeur's Hermeneutic Retrieval of Exodux 3:14 - Artner, Stephen (2025)
This paper responds to the phenomenological critique of ontotheology enacted by Heidegger and developed by Levinas and Marion. It asks the question: is it possible, as these thinkers would claim, to speak of God without any recourse to the language of being? The paper defends Paul Ricœur's stance on the matter, namely, that even though the Heideggerian break between God and Being is definitive, nevertheless it is impossible to fully escape the language of Being when speaking of God. And yet in the face of the Heideggerian critique, Being must be understood in new ways. The conjunction of God and Being was an event in history enacted by the Septuagint translation of Exodus 3:14 from Hebrew into Greek, thereby yoking together Hebrew revelation with Hellenic metaphysics. Mindful of the Heideggerian and Levinasian critique, one must take care not to limit the divine name by applying an abstracting Greek metaphysics onto it, but on the contrary let the divine self-revelation in the Hebrew text add further layers to the already rich semantic field of meaning contained in the Greek notion of being. Thus, the death of the metaphysical God through Nietzsche, Heidegger, Levinas, and Marion has in fact opened up the space for a hermeneutic retrieval of the Hebraic hyh that will continue to add new meaning to the polysemy of being for as long as Exodus 3:14 is still read.
Dieser Beitrag versteht sich als Antwort auf jene phänomenologisch grundierte Kritik der Ontotheologie, die von Heidegger vorgetragen und von Levinas und Marion aufgegriffen worden ist. Ist es möglich, wie diese Denker behaupten würden, von Gott zu sprechen, ohne auf die Sprache des Seins zurückzugreifen? Es soll der Standpunkt Paul Ricœurs verteidigt werden, dass der heideggersche Bruch zwischen Gott und Sein zwar endgültig, es aber dennoch unmöglich ist, in der Rede von Gott der Sprache des Seins völlig zu entkommen. Angesichts der heideggerschen Kritik muss die Rede vom Sein auf neue Weise verstanden werden. Die Verquickung von Gott und Sein war ein historisches Ereignis, das durch die Septuaginta-Übersetzung von Exodus 3,14 und die Zusammenblendung von hebräischer Offenbarung und hellenischer Metaphysik initiiert wurde. In Anbetracht der heideggerschen und levinasianischen Kritik ist darauf zu achten, den göttlichen Namen nicht durch eine abstrakte griechische Metaphysik zu verkennen, sondern im Gegenteil die im Hebräischen artikulierte göttliche Selbstoffenbarung durch weitere Schichten des bereits an sich reichhaltigen semantischen Bedeutungsfeldes des griechischen Seinsbegriffs anzureichern. So hat der Tod des metaphysischen Gottes durch Nietzsche, Heidegger, Levinas und Marion in der Tat den Raum für eine hermeneutische Wiedergewinnung des hebräischen hyh eröffnet, die der Polysemie des Seins so lange neue Bedeutung verleihen kann, wie Exodus 3,14 gelesen wird.
Keywords: God; Metaphysics; open spaces; Polysemy; Self-disclosure